Efeito adjuvante da lectina de Canavalia brasiliensis no tratamento de Leishmaniose cutânea experimental - Frutuoso, Mércia Sindeaux (2017)
The leishmaniases are importante public health problem, comprising a very wide spectrum of clinical presentations. The host protection and cure, depend on his or her capacity to mount an imune response type Th1, and IFN-γ is a key molecule on this protective response. The drugs of first choice for the treatment are the pentavalent antimonials, which cause several side effects and the most concerning side effect is the cardiotoxic ones. On the search for alternative treatment, fluconazole has shown promising results, however it has to be given for a longer time and in higher doses to achieve a better response. The Canavalia brasiliensis lectin (ConBr) has been described as a potent immune modulator, as it induces lymphocytic proliferation, with the production of IFN-γ. Based on these data we studied, if ConBr would potentiate the effect of fluconazole on the treatment of experimental cutaneous leishmaniasis, caused by L. braziliensis. To evaluate this, BALB/c mices (n=40) were infected with L. braziliensis and were divide randomly 10 days post-infection, in 5 groups, with the following treatments: 1- fluconazole (30mg/Kg/day/10days, per os); 2- Glucantime® (60mg/Kg/day/10days, intramuscular); 3- ConBr (10μg/50μl/day/5days, intramuscular); 4- Fluconazole (30mg/Kg/day/10days, per os) plus ConBr (10μg/50μl/day/5days, intramuscular); 5- Saline solution per os. The parameters evaluated on the 200 day post infection were: the thickness of the lesion every third day; parasite load on the draining lymph node; production of IFN-γ, IL-10, and TGF-β in cell culture of the draining lymph node supernatant, stimulated in vitro with promastigotes of L. braziliensis; relative liver and spleen weight and histopathological analysis of the lesions. Animals that were treated with the association of fluconazole and ConBr, when compared with those treated with saline solution, presented a significant reduction on the parasite load on the draining lymph nodes (p=0,006), reduction in lesion size (p=0,03) and higher production of IFN-γ on the supernatant of cell culture of regional lymph nodes (p=0,03). Similar data were observed on the group treated with Glucantime®, and all together, demonstrate that the association of fluconazole and ConBr was capable of inducing a therapeutic response similar to the one seen in the group treated with Glucantime®, which is considered the gold standard in the treatment for leishmaniasis.